In the Province of the Gods - Fries, Kenny (The University of Wisconsin Press, 2021)
Kenny Fries embarks on a journey of profound self-discovery as a disabled foreigner in Japan, a society historically hostile to difference. As he visits gardens, experiences Noh and butoh, and meets artists and scholars, he also discovers disabled gods, one-eyed samurai, blind chanting priests, and A-bomb survivors. When he is diagnosed as HIV positive, all his assumptions about Japan, the body, and mortality are shaken, and he must find a way to reenter life on new terms.